The top-down strategies in an EFL class of the vocational high school: an experimental study on enhancing students - Badrun Larandang; Nur Sehang Thamrin; Andi Naniwarsih; Fikriani Aminun Omolu; Nadrun Nadrun (Universitas Islam Negeri Palangka Raya, Indonesia, 2023)
Despite numerous studies emphasizing the benefits of using background knowledge and vocabulary in EFL listening courses, there is a lack of rationale for implementing top-down strategies that holistically integrate prior knowledge, vocabulary enhancement, and self-assessment. In order to address the issues, this study aimed to investigate the effectiveness of the teacher's top-down strategies in improving students' listening skills. Therefore, we utilized pre-experimental research, particularly a one-group pretest-posttest design, to ascertain the strategies